Performance and testing of the improved solar electric cooking system - Akter, Ayesha; Haque, Md. Minhaz Masrur; Ahmed, Sheikh Faiyaz (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.